Model Collaborative Governance dalam Pengelolaan Sampah Plastik Laut Guna Mewujudkan Ketahanan Maritim di Indonesia - Hidayat Chusnul Chotimah; Muhammad Ridha Iswardhana; Lucitania Rizky (Universitas Gadjah Mada, 2021)
Plastic pollution waste has become one of the world crisis that moves transboundary. Once at sea, plastic waste breaks down into small particles, so-called, microplastics are spread the marine ecosystems. It threatens human health and has harmful economic consequences for the marine sector. Indonesia is the second-largest contributor to the abundance of plastic waste in the ocean which in the same time as an archipelago country which rich in marine products. Indonesia is taking proactive steps as the responsible act for overcoming challenge of marine plastic pollution. So, the maritime environment resilience can be realized through a collaborative governance approach. This study uses a qualitative approach by collecting data from interviews, webinars and literature studies. The results of the study indicate that a collaborative governance approach is crucial to address marine plastic pollution by involving collaborating action from multi-stakeholders, government and non-government actors. Plastic pollution waste could be accomplished by strengthening the role and responsibility of each actor. In the process of collaboration, there are some dialogues, trust between the collaborating actors, commitment to the process of collaboration, shared understanding towards the common idea or goals, and intermediate outcome of collaboration between stakeholders in marine plastic waste management.